2016
DOI: 10.5223/pghn.2016.19.3.175
|View full text |Cite
|
Sign up to set email alerts
|

Henoch-Schonlein Purpura in Children Hospitalized at a Tertiary Hospital during 2004-2015 in Korea: Epidemiology and Clinical Management

Abstract: PurposeTo investigate the epidemiology, clinical manifestations, investigations and management, and prognosis of patients with Henoch-Schonlein purpura (HSP).MethodsWe performed a retrospective review of 212 HSP patients under the age of 18 years who were admitted to Inje University Sanggye Paik Hospital between 2004 and 2015.ResultsThe mean age of the HSP patients was 6.93 years, and the ratio of boys to girls was 1.23:1. HSP occurred most frequently in the winter (33.0%) and least frequently in the summer (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
34
3
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 37 publications
5
34
3
2
Order By: Relevance
“…Among patients with HSP, the risk of developing arthritis was reported to be highest in children up to 7 years of age, 2 as in our study. A pronounced gender predominance for HSP occurrence was not reported in other studies, 1,2,7 whereas in our study, arthralgia was slightly more predominant among boys.…”
Section: Discussioncontrasting
confidence: 89%
See 4 more Smart Citations
“…Among patients with HSP, the risk of developing arthritis was reported to be highest in children up to 7 years of age, 2 as in our study. A pronounced gender predominance for HSP occurrence was not reported in other studies, 1,2,7 whereas in our study, arthralgia was slightly more predominant among boys.…”
Section: Discussioncontrasting
confidence: 89%
“…7 In Korea, younger children are more at risk of developing arthritis, according to a nationwide populationbased study, 3 and affected children younger than 7 years had frequent joint symptoms. 2 Our results also demonstrated that the rate of arthralgia was highest among children aged 2-5 years (51.6%) and decreased with age (32.3% of patients aged 6-10 years and 16.1% of those aged 11-17 years).…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations